Analysis of Decision Support System to Determine Toddlers Eligible for Additional Food at Posyandu in Perkebunan Tanah Datar Village Using Profile Matching Method - Revina Salsabila; Nurul Rahmadani; Muhammad Iqbal (International Journal of Management Science and Information Technology, 2026)
The determination of toddlers eligible for the Supplementary Feeding Program (PMT) at the Integrated Health Post in Perkebunan Tanah Datar Village is still conducted manually, which can lead to subjectivity and inaccurate targeting of assistance. This study aims to develop a Decision Support System using the Profile Matching method to determine priority PMT recipients in a more objective and systematic manner. The assessment compares the actual condition of toddlers with an ideal profile by calculating GAP values across several criteria, including stunting status, nutritional status, parents’ income, and mother’s education level. These criteria are processed using Core Factor (60%) and Secondary Factor (40%) weighting to generate priority rankings. The system evaluation was conducted using seven toddler data samples, producing ranking results in which toddler B6 obtained the highest priority score of 4.5. The results indicate that the proposed method is able to generate consistent eligibility rankings and support a more transparent and measurable decision-making process compared to manual selection. By automating the calculation of GAP values and weighting factors, the system reduces subjectivity and improves the efficiency and accuracy of PMT recipient determination. However, this study is limited by the relatively small dataset and its implementation in a single Posyandu location. Future research may involve larger datasets and additional evaluation criteria to improve the robustness and applicability of the model in broader community health service settings.